Impact of irrigation technology use on crop yield, crop income and household food security in Nigeria: a treatment effect approach - Ogunniyi, A.; Omonona, B.; Abioye, O.; Olagunju, K. (American Institute of Mathematical Sciences, 2018)
Using household survey data from a sample of about 2305 households selected from eighteen states in Nigeria, this paper analyses the impact of irrigation technology usage on crop yield, crop income and household food security in Nigeria among smallholder farmers. The logistic regression estimate revealed that years of education, household size, rainfall information, access to credit, regional dummies are the main drivers of usage decision. The results of the linear regression with endogenous treatment effects showed that irrigation technology use is positively related to crop yield, crop income and household food security. In consistence, the impact analysis using propensity score matching (PSM) also showed a significant and positive effect of irrigation technology use on crop yield, crop income and household food security. We suggest to policy makers, implementers, and any funding agencies with similar interest to further capitalize and scale up the irrigation technology facilities, especially for the poor households, and create more awareness to improve the livelihood of rural households. However, despite the positive impact of irrigation technology use, we contend that other sustainable irrigation sources, such as rainwater harvesting should be used due to possible environmental impact in the excessive use of irrigation technology. Moreover, rained agriculture can be improved with other farming techniques such as agroforestry and soil and water conservation practices.